Expanding opportunities for chronic disease prevention for Hispanics: the Better Together REACH program in Pennsylvania - Calo, William A.; Aumiller, Betsy; Murray, Andrea; Crawford, Laurie; Bermudez, Madeline; Weaver, Lisa; Henao, Maria Paula; Gray, Nicole Maurer; DeLoatch, Vicki; Rivera-Collazo, Darilyn; Gomez, Janelle; Kraschnewski, Jennifer L. (Frontiers in Public Health, 2023)
Background: Hispanics in Lebanon and Reading, Pennsylvania, experience high levels of socioeconomic and health disparities in risk factors for chronic disease. In 2018, our community-academic coalition “Better Together” received a Racial and Ethnic Approaches to Community Health (REACH) award to improve healthy lifestyles. This report describes our work-in-progress and lessons learned to date from our REACH-supported initiatives in Lebanon and Reading. Methods: For the past four years, our coalition has leveraged strong community collaborations to implement and evaluate culturally-tailored practice- and evidence-based activities aimed at increasing physical activity, healthy nutrition, and community-clinical linkages. This community case report summarizes the context where our overall program was implemented, including the priority population, target geographical area, socioeconomic and health disparities data, community-academic coalition, conceptual model, and details the progress of the Better Together initiative in the two communities impacted. Results: To improve physical activity, we are: 1) creating new and enhancing existing trails connecting everyday destinations through city redesigning and master planning, 2) promoting outdoor physical activity, 3) increasing awareness of community resources for chronic disease prevention, and 4) supporting access to bikes for youth and families. To improve nutrition, we are: 1) expanding access to locally-grown fresh fruit and vegetables in community and clinical settings, through the Farmers Market Nutrition Program to beneficiaries of the Women, Infants, and Children (WIC) program and the Veggie Rx to patients who are at risk for or have diabetes, and 2) providing bilingual breastfeeding education. To enhance community-clinical linkages, we are training bilingual community health workers to connect at-risk individuals with diabetes prevention programs. Conclusions: Intervening in areas facing high chronic disease health disparities leads us to develop a community-collaborative blueprint that can be replicated across Hispanic communities in Pennsylvania and the United States.